2003
DOI: 10.17221/3496-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Changes of starch during microwave treatment of rice

Abstract: Rice (Oryza sativa L.), a major cereal crop, is the staple food source for half of the world population. Rice is an excellent source of energy, in the form of starch, and it gives the benefit of providing proteins with a higher nutritional quality than those of other cereal grains (M���������� et al. 1998). At present, many possible applications of microwave (MW) energy in the food industry are known. MW drying was demonstrated to be an alternative means for the rice drying (W�������� & K����� 1986). Major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 2 publications
0
18
1
3
Order By: Relevance
“…Conversely, in the Table 3, the factor cooking time caused changes in the starch structure of all genotypes of red rice studied, altering significantly the rheological behavior of the pregelatinized flours, reducing the peak viscosity and retrogradation, with irregular behavior of the viscosity breakdown. Pinkrová et al, (2003) and Yu & Wang (2007) also noted this type of viscous behaviour, but for rice starch irradiated in microwave oven and with gamma rays, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…Conversely, in the Table 3, the factor cooking time caused changes in the starch structure of all genotypes of red rice studied, altering significantly the rheological behavior of the pregelatinized flours, reducing the peak viscosity and retrogradation, with irregular behavior of the viscosity breakdown. Pinkrová et al, (2003) and Yu & Wang (2007) also noted this type of viscous behaviour, but for rice starch irradiated in microwave oven and with gamma rays, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…Instead, longer treatments (4 min) induced the opposite effect, and a decrease in the viscosity was noted. A decrease of the maximum (peak) viscosity was also observed by Pinkrová et al (2003) by increasing temperature of microwave treatment of the rice grain and increasing power output at a moisture content of 30 %. Roman et al (2015) have examined the effect of MW on flour structure.…”
Section: Pasting Properties Of Floursmentioning
confidence: 78%
“…These authors reported rearrangements of the molecular structure upon microwave heating that could explain the significant changes in viscosity properties of both waxy and non-waxy starches. Pinkrová et al (2003) have observed that the peak viscosity of rice flour decreased as temperature and microwave power level applied to rice grain increased. On the other hand, Fan et al (2012) reported that microwave irradiation had no effect on the optical and thermal properties of rice starch during gelatinization compared to conventional heating.…”
Section: Pasting Properties Of Floursmentioning
confidence: 99%
“…Rearrangements of the molecular structure during microwave heating produced significant changes in viscosity properties of both waxy and non-waxy starches. Furthermore, Pinkrová et al (2003) reported that the peak viscosity of rice flour decreased as temperature and microwave power level applied to rice grain increased.…”
Section: Introductionmentioning
confidence: 99%